The Rational Numbers in Three Moments of the History of Brazilian School Mathematics Os Números Racionais em Três Momentos da História da Matemática Escolar Brasileira - Maria Laura Magalhães Gomes (Universidade Estadual Paulista, 2008)
In this article we describe and analyze the approach given to the rational number concept in secondary school mathematics in Brazil through the examination of some textbooks published in the period from 1900 to1970. Three different moments are focused: 1) the first three decades of the twentieth century; 2) from 1931 to 1960; 3) the sixties and the first half of the seventies. We emphasize the differences found among those moments and try to characterize the prevailing approach in each one of them. Keywords: Rational Numbers. Mathematics Textbooks. History of Brazilian School Mathematics. Neste artigo, focalizamos a apresentação dos números racionais na matemática da escola secundária brasileira no século XX, até os anos 70, a partir da análise de alguns livros didáticos editados e utilizados nesse período. Destacamos três momentos: 1) as três primeiras décadas do século; 2) da Reforma Francisco Campos (1931) até o início dos anos 60; 3) os anos 60 e o início dos anos 70 - período de penetração e difusão do movimento da matemática moderna em nosso país. Assinalamos as diferenças entre os três momentos, buscando caracterizar a abordagem adotada em cada um deles. Palavras-chave: Números Racionais. Livros Didáticos de Matemática. História da Matemática Escolar no Brasil.